2009
DOI: 10.1364/josab.26.00b148
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the zero-diffraction regime in optical cavities with a left-handed material

Abstract: The combination of right-handed and left-handed materials offers the possibility to design devices in which the mean diffraction is zero. Such systems are encountered, for example, in nonlinear optical cavities, where a true zero-diffraction regime could lead to the formation of patterns with arbitrarily small sizes. In practice, the minimal size is limited by nonlocal terms in the equation of propagation. We study the nonlocal properties of light propagation in a nonlinear optical cavity containing a right-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…TLSs may, therefore, be used for signal processing, since the addition or the removal of a TLS simply means the change from one solution to another. Note that the same model equation (2.1) using fourth-order diffraction instead of dispersion has previously also been proved to support higher-order spatial effects on bright spatial solitons [41,42]. Moving TLSs involving multipeak solutions are shown in figure 5.…”
Section: Subcritical Modulational Instability and Temporal Localized Structuresmentioning
confidence: 78%
“…TLSs may, therefore, be used for signal processing, since the addition or the removal of a TLS simply means the change from one solution to another. Note that the same model equation (2.1) using fourth-order diffraction instead of dispersion has previously also been proved to support higher-order spatial effects on bright spatial solitons [41,42]. Moving TLSs involving multipeak solutions are shown in figure 5.…”
Section: Subcritical Modulational Instability and Temporal Localized Structuresmentioning
confidence: 78%
“…They also allow for phase compensation in optical structures containing both left-and right-handed materials. Recently, it has been shown that such materials could be used to improve telecommunication systems by lowering power threshold and increasing data density in optical memories [121][122][123][124]. More recently, an exprimental evidence of localized structure in left-handed materials has been provided [125].…”
Section: Localized Structures In Photonic Crystals Left-handed Materi...mentioning
confidence: 99%
“…It means that the PBGs not only suffer from the errors from manufacturing, but also cannot be tuned as the constituents and topologies of PCs are certain. To overcome such drawbacks, metamaterials are introduced into the conventional PCs to obtain the tunable PBGs [9][10][11]. Metamaterials are firstly proposed theoretically by Veselago in 1968 [12], which can also be called left-hand materials due to their unusual physical properties such as inverse Snell's law, negative refraction index, Cherenkov effects and reversed Doppler effect.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitriadis et al [20] developed a accurate matrix surface susceptibility model for the homogenization of metasurfaces under oblique T E plane wave incidence, and they proclaimed that the efficiency of the model is contingent upon the electrical size of the scatterers rather than the lattice periodicity. Epsilon-negative (ENG) materials can be looked as a kind of metamaterials [9][10][11], in which permittivity ε is negative, but permeability µ is positive. However, if µ and ε are negative, the double-negative (DNG) metamaterial can be obtained.…”
Section: Introductionmentioning
confidence: 99%